(untitled) (The Planet, 2025)
Background: Childhood obesity is a major concern in Bangladesh, as in many parts of the world. With socio-economic transition and rapid urbanization in recent years, the prevalence of childhood obesity in Bangladesh is expected to rise. This study was designed to see the prevalence and risk factors of childhood obesity among school children in Sylhet. Methods: A cross-sectional study was conducted among students of class six to ten of four rural high schools. Demographic and anthropometric data were collected and BMI was calculated. The students were categorized as underweight, normal weight and overweight and obese based on International Obesity Task Force (IOTF) cutoff values. Logistic regression analysis was done to see the association of various factors with childhood obesity. P value of ≤ 0.05 was taken a significant. Results: Total 587 students were included in this study. Age varied from 10 to 18 years. Among them 10.9% and 3.6% were found to be overweight and obese respectively. Obesity was significantly higher among girls than boys (17.7% versus 11.1%). Low level (2 hours/day) screen time and consumption of fast food were found to be associated with childhood obesity. Breakfast skipping, mode of transport to school and sleep duration were not found as significant risk factors of obesity. Conclusion: Prevalence of overweight and obesity is high among rural school children in Sylhet. Obesity is higher among girls. Fast food, high screen time and less physical activity are important factors of childhood obesity.